Taking a seat at the table: The value of private higher education in South Africa - Meyer, L. (South African Journal of Higher Education, 2025)
In marketing, perception is reality. This scholarly discourse investigates the inherent bias manifested in the perceived disparity between qualifications conferred by private higher education institutions and public universities within the South African context. It is argued that Private Higher Education Institutions (PHEIs) are integral to the education system. Government funding for students who elect to study at a PHEI would be a strategic investment in the nation's future. The article begins with a summation of the higher education (HE) landscape in South Africa, highlighting the target student enrolment numbers set by the National Development Plan 2030 and the need for additional investment in the sector in its entirety. The article raises the question of what makes a qualification from one institution more valuable than a qualification from another registered within the same quality assurance and accreditation framework where students can articulate from private to public Institutions and vice versa. Furthermore, the article explores the constraints experienced by students eligible for financial assistance but excluded from eligibility by the National Student Financial Aid Scheme (NSFAS) when electing to study at a PHEI. The article emphasises the significance of addressing these biases and advocates for promoting the equitable treatment of PHEIs and public universities within the domestic HE landscape. The article highlights the need to improve access to HE and foster social justice in the South African HE system.